Characterization of Low-Molecular Weight Iodine-Terminated Polyethylenes by Gas Chromatography/Mass Spectrometry and Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry with the Use of Derivatization. Issue 3 (June 2013) - Zaikin, Vladimir G.; Borisov, Roman S.; Polovkov, Nikolai Yu.; Zhilyaev, Dmitry I.; Vinogradov, Aleksei A.; Ivanyuk, Aleksei V.
Gas chromatography/mass spectrometry (GC/MS) and matrix-assisted laser desorption/ionization time-of-flight (MALDI-ToF) mass spectrometry, in conjunction with various derivatization approaches, have been applied to structure determination of individual oligomers and molecular-mass distributions ( MMD ) in low-molecular mass polyethylene having an iodine terminus. Direct GC/MS analysis has shown that the samples under investigation composed of polyethyelene-iodides (major components) and n -alkanes. Exchange reaction with methanol in the presence of NaOH gave rise to methoxy-derivatives and n -alkenes. Electron ionization mass spectra have shown that the former contained terminal methoxy groups indicating the terminal position of the iodine atom in the initial oligomers. MMD parameters have been determined with the aid of MALDI mass spectrometry followed by preliminary derivatization-formation of covalently bonded charge through the reaction of iodides with triphenylphosphine, trialkylamines, pyridine or quinoline. The mass spectra revealed well-resolved peaks for cationic parts of derivatized oligomers allowing the determination of MMD . The latter values have been compared with those calculated from GC/MS data.